2022
DOI: 10.3389/fonc.2022.1000993
|View full text |Cite
|
Sign up to set email alerts
|

A novel signature of combing cuproptosis- with ferroptosis-related genes for prediction of prognosis, immunologic therapy responses and drug sensitivity in hepatocellular carcinoma

Abstract: BackgroundOur study aimed to construct a novel signature (CRFs) of combing cuproptosis-related genes with ferroptosis-related genes for the prediction of the prognosis, responses of immunological therapy, and drug sensitivity of hepatocellular carcinoma (HCC) patients.MethodsThe RNA sequencing and corresponding clinical data of patients with HCC were downloaded from The Cancer Genome Atlas (TCGA), International Cancer Genome Consortium (ICGC), GSE76427, GSE144269, GSE140580, Cancer Cell Line Encyclopedia (CCLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
1
14
1
Order By: Relevance
“…In addition, Wang and Zhao et al. found that G6PD could be used for building models of hepatocellular carcinoma ( 22 , 23 ). All of the above studies indicate that G6PD and the development of hepatocellular carcinoma are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Wang and Zhao et al. found that G6PD could be used for building models of hepatocellular carcinoma ( 22 , 23 ). All of the above studies indicate that G6PD and the development of hepatocellular carcinoma are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 has been shown to be a tumor suppressors in regulating metabolism of tumor cells ( 40 , 41 ). Nevertheless, HCC tissues with TP53 mutation could detect the vascular invasion and angiogenesis, and these tissues are characterized by hypodifferentiation ( 42 , 43 ). CTNNB1 gene encodes the protein β-catenin which has been found could promote immune escape and may affect the immunotherapy in HCC ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence have provided a robust connection between iron- and copper-dependent cell death across many cancers. For instance, in hepatocellular carcinoma and lung adenocarcinoma, the reciprocity between regulators of ferroptosis and cuproptosis elucidates the tumor microenvironment, which ultimately governs prognosis and sensitivity for chemotherapeutics [ 132 , 133 ]. Apart from the association of cuproptosis and ferroptosis with cancer, further studies have significantly uncovered their interplay.…”
Section: Cuproptosis: a Copper-mediated Programmed Cell Deathmentioning
confidence: 99%